Association of seed mycoflora with peas Pisum sativa L. seeds - khani, Sidra Qaim; Khaskheli, M. Ibrahim; Jiskani, M. Mithal; Nizamani, Imtiaz A.; Khaskheli, Allah Jurio; Chang, Xiaoli; Anum, Aisha (International Journal of Environment, Agriculture and Biotechnology, 2019)
Seed is a vital source for producing optimum yield. Seed-borne pathogens may cause losses by reducing seed germination, developing seed-borne diseases and mortality of seedlings in nursery beds. However, knowledge of the about the biology and extent of seed-borne pathogens and thereafter practices for their management can help to reduce seed and seedling losses. Thus, present studies were conducted to find out the association of seed associated mycoflora with major vegetable peas in the laboratories of Department of Plant Protection, Sindh Agriculture University and Federal Seed Certification and Registration Department, Karachi, Sindh, Pakistan from February to October 2017. Total of 10 different fungal species belonging to different genera was isolated from peas seeds through blotter paper and agar plate methods. Significantly highest frequency percent for Alternariaalternata (50%), Aspergillus fumigates (48.33%), A. niger (36.67%), A. flavus (23.33%), C. lunata (17.5%) and F. oxysporum (17.5%). However, the lowest frequency was recorded for T. viride (4.17%), R. stolonifer (5%), Penicillium sp. (5.83%) and Stemphylium (11.67%) through the agar plate method. A similar trend of frequency was noticed for blotter paper in all recorded fungi; however, the extent was lower compared to the agar plate method. The results of the present studies provide the baseline information about seed mycoflora for further studies and management of seed-borne diseases associated with peas seeds.